2018
DOI: 10.3233/jad-180485
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Apathy Scales in Dementia: A Systematic Review

Abstract: Apathy is a prevalent and problematic neuropsychiatric symptom in those with dementia that is emerging as a treatment target, necessitating accurate assessment. While many apathy scales are available, not all have been developed for use exclusively in dementia, and psychometric properties may vary across different populations. This systematic review aimed to provide an overview of the psychometric properties of apathy scales used in Alzheimer's disease (AD) and related dementias, as well as rate the methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 57 publications
0
19
0
1
Order By: Relevance
“…Future studies will have the opportunity to disentangle the contribution of each apathy sub-type by using appropriate clinical instruments, which give more detail than the NPI. Although the NPI is among the scales most often used to assess apathy in AD, other validated instruments relying on a different methodology exist, such as the Apathy Evaluation Scale (Mohammad et al, 2018). Three versions of this scale exist, and a study carried out in healthy adults and patients with MCI found a significant association between clinician-rated levels of apathy and thickness of the inferior temporal cortex (Guercio et al, 2015), a region that is not part of the theoretical frameworks this study is based upon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies will have the opportunity to disentangle the contribution of each apathy sub-type by using appropriate clinical instruments, which give more detail than the NPI. Although the NPI is among the scales most often used to assess apathy in AD, other validated instruments relying on a different methodology exist, such as the Apathy Evaluation Scale (Mohammad et al, 2018). Three versions of this scale exist, and a study carried out in healthy adults and patients with MCI found a significant association between clinician-rated levels of apathy and thickness of the inferior temporal cortex (Guercio et al, 2015), a region that is not part of the theoretical frameworks this study is based upon.…”
Section: Discussionmentioning
confidence: 99%
“…The Neuropsychiatric Inventory (NPI) 2 is a quantitative scale which estimates presence, frequency and severity of twelve psychiatric symptoms (listed in Table 1) from the point of view of a caregiver (Cummings, 1997). It is among the clinical instruments most often used to assess the presence of apathy in AD (Mohammad et al, 2018), and has adequate levels of test-retest reliability (Kaufer et al, 2000). The informants were asked to complete the entire NPI but, for the purpose of this study, only the apathy section of the questionnaire was used as predictor for inferential modelling.…”
Section: 2measurement Of Apathy and Other Neuropsychiatric Symptomsmentioning
confidence: 99%
“…A general trend toward the use of Apathy Evaluation Scale (AES) and/or the aNPI have been reported. 5,34,35 A few studies have shown a positive correlation between aNPI and AES score in patients with AD. 5,10,34 In order to identify and quantify apathy, we used aNPI that is equally sensitive and less time consuming compared to AES 34,36 and is more widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most frequent behavioral syndrome in neurological and psychiatric diseases, such as Alzheimer's disease (AD), Parkinson's disease, stroke and schizophrenia (310). Apathy is usually assessed by questionnaires (scales) administered to the patient and/or caregiver and providing information about the patient's internal state, thoughts and past activities, globally suggesting a loss of motivation to perform daily activities (11, 12). However, these scales are biased by the subjective nature of the patient or caregiver's perspective (13).…”
Section: Introductionmentioning
confidence: 99%